Induced Cell Cycle Arrest in Triple-Negative Breast Cancer by Combined Treatment of Itraconazole and Rapamycin - Wu, Hua-Tao; Li, Chun-Lan; Fang, Ze-Xuan; Chen, Wen-Jia; Lin, Wen-Ting; Liu, Jing (Frontiers in Pharmacology, 2022)
Triple-negative breast cancer (TNBC) is the aggressive molecular type of breast carcinoma, with a high metastasis/relapse incidence and cancer-related death rate, due to lack of specific therapeutic targets in the clinic. Exploring potential therapeutic targets or developing novel therapeutic strategies are the focus of intense research to improve the survival and life quality of patients with TNBC. The current study focused on drugs targeting the mTOR signaling pathway by investigating the potential utilization of itraconazole (ITZ) combined with rapamycin in the treatment of TNBC. CCK-8, colony formation and transwell assays were conducted to evaluate the effect of ITZ with rapamycin in combination on MDA-MB-231 and BT-549 TNBC cells. Synergistic inhibition was found in terms of proliferation and motility of TNBC cells. However, apoptosis was not enhanced by the combined treatment of ITZ and rapamycin. Flow cytometry analysis showed that ITZ and/or rapamycin arrested cells in G0/G1 phase and prevented G1/S phase transition. Reduced cyclin D1 protein levels were consistent with G0/G1 phase arrest, especially when resulting from the combination of ITZ with rapamycin. In conclusion, the combination of ITZ with rapamycin is a promising therapeutic strategy for patients with TNBC through synergistically arresting cells in the G0/G1 phase of the cell cycle, rather than inducing apoptosis.